2019
DOI: 10.1530/erc-18-0383
|View full text |Cite
|
Sign up to set email alerts
|

KLF14 potentiates oxidative adaptation via modulating HO-1 signaling in castrate-resistant prostate cancer

Abstract: Insights into the mechanisms by which key factors stimulate cell growth under androgen-depleted conditions is a premise to the development of effective treatments with clinically significant activity in patients with castration-resistant prostate cancer (CRPC). Herein, we report that, the expression of Krüppel-like factor 14 (KLF14), a master transcription factor in the regulation of lipid metabolism, was significantly induced in castration-insensitive PCa cells and tumor tissues from a mouse xenograft model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Despite lower antioxidant capacity as compared with normal cells, PCa cells adaptively synthesize more antioxidants like HO-1, Nrf2, and GPXs to cope with the continued ROS production. A wealth of studies have suggested that under the dynamic nonequilibrium of ROS, elevated antioxidant genes facilitate the maintenance of protumorigenic signaling and protect against oxidative-dependent death within tumor cells [ 56 ]. There is a 45% failure of PCa patients after high-dose radiotherapy against localized diseases, which may be partially due to elevated basic Nrf2 gene expression essential to resist hazardous environmental insults [ 57 ].…”
Section: Cellular Detoxification From Ros Of Pcamentioning
confidence: 99%
See 1 more Smart Citation
“…Despite lower antioxidant capacity as compared with normal cells, PCa cells adaptively synthesize more antioxidants like HO-1, Nrf2, and GPXs to cope with the continued ROS production. A wealth of studies have suggested that under the dynamic nonequilibrium of ROS, elevated antioxidant genes facilitate the maintenance of protumorigenic signaling and protect against oxidative-dependent death within tumor cells [ 56 ]. There is a 45% failure of PCa patients after high-dose radiotherapy against localized diseases, which may be partially due to elevated basic Nrf2 gene expression essential to resist hazardous environmental insults [ 57 ].…”
Section: Cellular Detoxification From Ros Of Pcamentioning
confidence: 99%
“…There is a 45% failure of PCa patients after high-dose radiotherapy against localized diseases, which may be partially due to elevated basic Nrf2 gene expression essential to resist hazardous environmental insults [ 57 ]. Overexpression of antioxidant gene KLF4 restores the redox balance of PCa cells and reduces ROS-dependent cell death induced by chemotherapy drugs, such as high concentrations of H2O2 and paraquat [ 56 , 58 ]. The silence of the KMTD2 gene could weaken the combination of antioxidant genes with FOXO3 DNA to downregulate the expressions of antioxidants, thereby enhancing the chemosensitivity of PCa cells [ 59 ].…”
Section: Cellular Detoxification From Ros Of Pcamentioning
confidence: 99%
“…The link between KLF proteins and regulation of cell cycle processes such as proliferation, differentiation, as well as cell adhesion and migration (15), and maintenance of pluripotency of stem cells (16) have been well established. More recently, several studies showed that KLFs also play important roles in cancer (14,109) [reviewed in (15)]. Stacey et al reported a new genomic locus associated with increased susceptibility to basal cell carcinoma (BCC) (110).…”
Section: The Role Of Klf14 In Cancer and Placenta Developmentmentioning
confidence: 99%
“…However, the newest report of Luo XH suggested that KLF14 might have complete opposite function in different types of tumors. They found that KLF14 potentiate oxidative adaptation in castrate‐resistant prostate cancer via modulating heme oxygenase‐1 signaling and subsequently induce tumor growth …”
Section: Klf14 and Tumorigenesismentioning
confidence: 99%
“…They found that KLF14 potentiate oxidative adaptation in castrate-resistant prostate cancer via modulating heme oxygenase-1 signaling and subsequently induce tumor growth. 45…”
Section: Klf14 and Tumorigenesismentioning
confidence: 99%